Attitudes and perceptions towards vulvar and vaginal atrophy in Italian post-menopausal women: Evidence from the European REVIVE survey. (September 2016) - Nappi, Rossella E.; Particco, Martire; Biglia, Nicoletta; Cagnacci, Angelo; Di Carlo, Costantino; Luisi, Stefano; Paoletti, Anna Maria
Highlights: An analysis is reported of the characteristics and variability of vaginal health perception for an Italian sample of post-menopausal women. Vulvo-vaginal symptomatology had a significant impact on participants' sexual life. Treatment dissatisfaction and abandonment were very common in Italian women with vaginal problems. Fluent interaction and dialogue with physicians would improve the management vaginal health in Italy. Abstract: Objectives: To achieve a deeper understanding of the attitudes and perceptions of Italian post-menopausal women (PMW) regarding vulvo-vaginal atrophy (VVA). Study design: As part of the EU REVIVE study, an online survey was conducted in four European countries; the Italian arm comprised 1000 participants from representative regions of Italy. Main outcome measures: The perceptions, experiences and needs of Italian PMW in relation to sexual and vaginal health. Results: The most frequent VVA symptom was vaginal dryness (78%). Usually, the severity of symptoms was similar to or worse than when they first appeared. This was particularly true for dyspareunia, the most bothersome symptom (76%). VVA symptoms had a significant impact on Italian participants' ability to achieve pleasurable relations (74%) and spontaneity (70%). Although 75% of participants were still sexually active, their sex drive had been reduced by a third because of VVA. Women expected that doctors would start a discussion of menopausal symptoms and sexual health, but this was rarely the case (11%). Most women had been treated with a vaginal over-the-counter (OTC) product. Women who had discussed their condition with a physician were more likely (68%) to be under treatment for VVA than those who had not (36%). Low compliance was associated with symptom improvement (23%), not having annoying symptoms (22%), and the impossibility if restoring the vagina to normal (14%). Common reasons for treatment dissatisfaction were related to route of administration or discomfort. Lack of efficacy and fear of a hormone effect were perceived as the main limitations for OTC and local estrogen products, respectively. Conclusions: Despite the commonness of VVA and its significant impact on quality of life, the condition remains underdiagnosed in Italy. Discussion of symptoms with doctors influences the diagnosis, and patients' satisfaction with available treatments is not high.